Insight Into the Role of PGPR in Sustainable Agriculture and Environment - Mohanty, Pratikhya; Singh, Puneet Kumar; Chakraborty, Debosmita; Mishra, Snehasish; Pattnaik, Ritesh (Frontiers in Sustainable Food Systems, 2021)
A multitude of roles is played by microbes in food and agriculture that include nutrient cycling and management, organic matter decomposition and fermentation. Plant growth promoting rhizobacteria (PGPR), representing microbial groups and with ability of colonising plant roots, influence plant growth through various indirect and direct modes in order to promote its growth and/or protect it from diseases or damage due to insect attack. Thus, PGPR research has received renewed interest worldwide. Increasing number of crop-specific PGPR are being commercialised these days. Approaches like seed-inoculation and soil application either alone or in combination with bacterial culture/product for increased nutrient availability through phosphate solubilisation, potassium solubilisation, sulphur oxidation, nitrogen fixation, iron and copper chelation are gaining popularity. Arbuscular mycorrhizal fungi (AMF) are root fungal symbiont that improve management of abiotic stress such as phosphorus deficiency. PGPR involves roles like production of indole acetic acid (IAA), ammonia (NH3), hydrogen cyanide (HCN), catalase, etc. PGPR also improve nutrient uptake by altering the level of plant hormone that enhances root surface area by increasing its girth and shape, thereby helping in absorbing more nutrients. PGPR facilitate seed germination, seedling growth and crop yield. An array of microbes including Pseudomonas, Azospirillum, Azotobacter, Klebsiella, Enterobacter, Alcaligenes, Arthrobacter, Burkholderia, Bacillus and Serratia enhance plant growth. Various Pseudomonas sp. have demonstrated significant increase in germination, seedling growth and yield in different agricultural crops, including wheat. Hence, developing a successful crop-specific PGPR formulation, the candidate should possess characteristics like high rhizosphere competence, extensive competitive saprophytic ability, growth enhancing ability, ease of mass production, broad-spectrum action, safety towards the environment and compatibility with other partnering organisms.